CASP3 protein expression by flow cytometry in Down’s syndrome subjects - Salemi, Michele; Condorelli, Rosita A.; Romano, Corrado; Concetta, Barone; Romano, Carmelo; Salluzzo, Maria Grazia; Bosco, Paolo; Calogero, Aldo E. (Human cell : official journal of Human Cell Research Society, 2014)
Down’s syndrome (DS), the most common chromosomal disorder, is caused by 21 trisomy and is featured by intellectual disability. Subjects with DS can develop some traits of Alzheimer disease (AD) at an earlier age than subjects without trisomy 21. Apoptosis is a programmed cell death process under both normal physiological and pathological conditions. Caspase-3 (CASP3) plays an important role in neuronal death during nervous system development and under certain pathological conditions. Furthermore, in vitro and in vivo studies report elevated expression and activation of CASP3 in models of AD. On this account, the expression of CASP3 gene was evaluated in cultures of fibroblasts of DS and normal subjects by flow cytometry. CASP3 protein was up-regulated in fibroblasts of DS. The data obtained from this study strengthen the hypothesis that the over-expression of CASP3 gene could have a role in the activation of the apoptotic pathways acting in the neurodegenerative processes in DS.